Three-dimensional geoelectric model of the Kirovograd ore area of the central part of the Ukrainian Shield - I. Nikolaev; T.K. Burakhovich; E. Sheremet (Геофизический журнал, 2013)
The authors give their 3D geoelectric model of the Kirovohrad ore district and consider aspects related to the association of uranium manifestations of albitite formation, gold fields and manifestations of graphite with anomalies of increased electrical conductance at the depths in the range of 0—100 m, 0,1—2,5 km, 2,5—20 km, 25—30 km  and 50—120 km.